TYPICAL FEATURES OF PRIMARY DRUG RESISTANCE AND VIABILITY OF MYCOBACTERIA IN TUBERCULOSIS PATIENTS WITH CONCURRENT HIV INFECTION - N. M. Koretskaya; I. A. Bolshakova (Туберкулез и болезни лёгких)
Goal: to study the structure, profile of primary drug resistance and viability of mycobacteria in tuberculosis patients with concurrent HIV infection.Materials and methods. Structure, profile of primary drug resistance and viability of mycobacteria were studied in 67 pulmonary tuberculosis patients with concurrent HIV infection.Results. It has been found out that new drug resistance tuberculosis in those suffering from HIV infection is characterized by severe structure of drug resistance with obvious predominance of multiple (73.1%) and extensive (16.4%) primary drug resistance combined with resistance to main and reserve TB drugs in the majority of cases. Nearly total primary drug resistance to isoniazid, streptomycin and rifampicin has been observed as well as severe burden of TB strains resistant to reserve drugs among which special attention is to be paid to resistance to ofloxacin, detected in the each 4th patient. The above features of drug resistance in tuberculosis patients with concurrent HIV infection create significant difficulties for compilation of the proper regimen of TB drugs for chemotherapy as per regimens IV and V thus inevitably deteriorating treatment efficiency and significantly increasing mortality of such patients.